The Effect of AI-Based Technology Implementation, Green Energy Sustainability, and Product Innovation on Economic Growth of the Manufacturing Industry in Indonesia - Loso Judijanto; Triyugo Winarko; Usman Tahir; Arnes Yuli Vandika; Amelia S. Sarungallo (West Science Nature and Technology, 2024)
This study investigates the effect of AI-based technology implementation, green energy sustainability, and product innovation on the economic growth of the manufacturing industry in Indonesia. Using a quantitative research approach, data were collected from 120 manufacturing firms and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results show that AI-based technology has the strongest positive impact on economic growth, followed by green energy sustainability and product innovation. AI-driven technologies optimize operations, reduce costs, and enhance decision-making, contributing significantly to the economic performance of firms. Green energy sustainability promotes long-term growth by reducing operational costs and improving environmental performance. While product innovation positively influences growth, its impact is relatively weaker, indicating the need for complementary factors. These findings provide insights for policymakers and industry leaders to focus on technological advancement, sustainability, and innovation as drivers of economic growth in Indonesia’s manufacturing sector.